Message from Editor in chief - Hacıfazlıoğlu, Özge (Birlesik Dunya Yenilik Arastirma ve Yayincilik Merkezi, 2022)
Dear reader, Thank you for showing interest in the Volume 17 Number 2, February 2022 issue of our Cypriot Journal of Educational Sciences (CJES). This publication aimed to present current methods of teaching and the responses of the stakeholders regarding the new methods. Based on the aim of this issue, 26 standard articles were selected.
Keywords: eğitim; Covid-19; pandemi